Blockade of transient receptor potential cation channel subfamily V member 1 promotes regeneration after sciatic nerve injury - Ren, Fei (Neural Regen Res, 2015)
The transient receptor potential cation channel subfamily V member 1 (TRPV1) provides the sensation of pain (nociception). However, it remains unknown whether TRPV1 is activated after peripheral nerve injury, or whether activation of TRPV1 affects neural regeneration. In the present study, we established rat models of unilateral sciatic nerve crush injury, with or without pretreatment with AMG517 (300 mg/kg), a TRPV1 antagonist, injected subcutaneously into the ipsilateral paw 60 minutes before injury. At 1 and 2 weeks after injury, we performed immunofluorescence staining of the sciatic nerve at the center of injury, at 0.3 cm proximal and distal to the injury site, and in the dorsal root ganglia. Our results showed that Wallerian degeneration occurred distal to the injury site, and neurite outgrowth and Schwann cell regeneration occurred proximal to the injury. The number of regenerating myelinated and unmyelinated nerve clusters was greater in the AMG517-pretreated rats than in the vehicle-treated group, most notably 2 weeks after injury. TRPV1 expression in the injured sciatic nerve and ipsilateral dorsal root ganglia was markedly greater than on the contralateral side. Pretreatment with AMG517 blocked this effect. These data indicate that TRPV1 is activated or overexpressed after sciatic nerve crush injury, and that blockade of TRPV1 may accelerate regeneration of the injured sciatic nerve.